Meningkatkan Hasil Belajar melalui Model Pembelajaran Kooperatif Tipe Talking Stick - lisnah pai (IQRO: Journal of Islamic Education, 2019)
This study discusses the application of the Talking Stick type Cooperative model in the Islamic Education Class IX3 class at SMP Negeri 8 Palopo with the subject of Al-Qur'an Hadith in the odd semester of the academic year 20172018. This research is Classroom Action Research. Learning outcomes data collected were analyzed using quantitative analysis and observational results were analyzed qualitatively. The study was conducted in two cycles each cycle carried out in 2 meetings with a total of 28 students consisting of 14 male students and 14 female students. Data retrieval is done by using observation sheets and test results of learning. The results showed the average learning outcomes of students before applying the Talking Stick 68.46 With classical learning completeness 75 after applying the Talking Stick model the results of the study showed the average learning outcomes of students in the first cycle was 79.25 and the cycle II of 88.53. Based on the results of this study it can be concluded that by applying it the Talking Stick model can improve the learning outcomes of Religious Education for Class IX3 Students of SMP Negeri 8 Palopo